Designing a District Energy Infrastructure - a Case-Study in Lisbon - Jewell, Alexandre; Schüler, Nils; Cajot, Sébastien; Gomes, Ricardo; Silva, Carlos Santos; Marechal, Francois M. A. (Frontiers in Sustainable Cities, 2022)
The paper describes a case study on the design of district energy infrastructure for the green-field project of the Vale de Santo António (Lisbon, Portugal). The methodology is based on a novel framework built on the sequential integration of three software tools: QGIS, City Energy Analyst (CEA) and Urbio. QGIS is used to define the building database (construction solutions, uses and schedules); CEA is used to model the neighbourhood energy services (heating, cooling, domestic hot water and electricity, including for EVs); and Urbio is used to design the energy infrastructure to supply the neighbourhood in an optimal manner. The study illustrates the high impact of building renovation on heat demand and the existing potential for a two-layout network to minimise pumping demand and heat distribution loss. Moreover, a sensitivity analysis with regard to future carbon tax changes and electricity greening concludes that an electricity-based heating mix is optimal.